Synaptic plasticity and roles of orexin in distinct domains of the olfactory tubercle - Podder, Sajib; Murata, Yoshihiro; Taniguchi, Mutsuo; Shimizu, Shogo; Yamaguchi, Masahiro (Frontiers in Neural Circuits, 2024)
Olfactory behavior is highly plastic, and the olfactory tubercle (OT), a component of the olfactory cortex and ventral striatum, includes anteromedial (amOT) and lateral (lOT) domains with roles in attractive and aversive olfactory behavioral learning, respectively. However, the underlying properties of synaptic plasticity in these domains are incompletely understood. Synaptic plasticity is regulated by multiple signals including synaptic inputs and neuromodulators. Interestingly, the amOT domain exhibits high expression of various receptors for neuromodulators. We investigated synaptic plasticity in mouse OT slices by combining electrical stimulation and treatment with the appetitepromoting neuropeptide orexin, the receptors of which are highly expressed in the amOT. In both the amOT and lOT, one round of 2-Hz burst stimulation elicited short-term potentiation of the field excitatory postsynaptic potential, whereas three rounds of stimulation induced long-term potentiation (LTP) that persisted for 150 min. In the amOT, orexin-A induced LTP was blocked by the orexin receptor type 1 antagonist SB334867. Orexin-A also facilitated LTP induction in the amOT by one round of 2-Hz burst stimulation. By contrast, these effects were not observed in the lOT. These results highlighted the similarity and difference in synaptic plasticity between the OT domains and suggested that orexin facilitates synaptic plasticity in the amOT during olfactory learning processes such as food odor learning.